Tandem ICP-mass spectrometry for Sr isotopic analysis without prior Rb/Sr separation. Issue 1 (10th July 2015) - Bolea-Fernandez, Eduardo; Balcaen, Lieve; Resano, Martín; Vanhaecke, Frank
Abstract : The use of CH3 F as a reaction gas in tandem ICP-mass spectrometry (ICP-MS/MS) enables the accurate determination of the 87 Sr/ 86 Sr isotope ratio in geological materials, provided that mass discrimination is corrected for by a combination of internal and external correction. Abstract : The use of a mixture of 10% of CH3 F and 90% of He as a reaction gas in tandem ICP-mass spectrometry (ICP-MS/MS) enables the accurate determination of the 87 Sr/ 86 Sr isotope ratio in geological materials, provided that mass discrimination is corrected for by using a combination of internal (Russell law, assuming a constant 88 Sr/ 86 Sr isotope ratio) and external correction (using the isotopic reference material NIST SRM 987 SrCO3 ) in a sample-standard bracketing approach. No prior Rb/Sr separation is required as the isobaric overlap at a mass-to-charge ratio of 87 is avoided by monitoring SrF + reaction product ions instead of Sr + ions. Rb shows no reactivity towards CH3 F. The double mass selection (MS/MS mode) prevents both spectral overlap from atomic ions at the mass-to-charge ratios of SrF + reaction product ions and a measurable effect from the matrix on the 87 Sr/ 86 Sr result. This aspect is critical, as it enables accurate results to be obtained without the need for using a matrix-matched standard to correct for mass discrimination, in contrast to previous work with a quadrupole ICP-MS instrument with a CH3 F/Ne-pressurized cell, in which the use of a matrix-matched standard was compulsory. The precision attainable – 0.05% RSD external precision – suffices for making the newly developed method useful in a variety of applications.